1992
DOI: 10.1002/1097-0142(19920515)69:10<2406::aid-cncr2820691004>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Early depressed adenocarcinomas of the large intestine

Abstract: From January 1987 to December 1990, five cases of early depressed cancer of the large intestine were seen. Endo‐scopically, almost all of these tumors were located in the proximal colon and looked like a reddish depression (similar to the sucker of an octopus). Histologically, all of these cancers were well differentiated and tended to reach deeper layers at an early stage. Four (80%) of these cancers were not associated with adenoma and were thought to have arisen de novo. Cancer 1992; 69:2406‐2410.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
57
0
2

Year Published

1993
1993
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(63 citation statements)
references
References 12 publications
4
57
0
2
Order By: Relevance
“…In the absence of this awareness, detection during routine examination may be difficult. 4 Bedenne et al 22 and Iishi 18 reported that de novo cancers were located predominantly in the right Figure 4. Incidence of depressed-and non-depressed-type early cancers in the rectum, left colon and right colon.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of this awareness, detection during routine examination may be difficult. 4 Bedenne et al 22 and Iishi 18 reported that de novo cancers were located predominantly in the right Figure 4. Incidence of depressed-and non-depressed-type early cancers in the rectum, left colon and right colon.…”
Section: Discussionmentioning
confidence: 99%
“…As more than 70% of FDNs show positive immunostaining of p-MAPK, this signalling pathway may play an important role in the tumorigenesis of FDNs. Many have reported CRCs arising from FDNs or nonpolypoid neoplasias (Shimoda et al, 1989;Bedenne et al, 1992;Iishi et al, 1992;Kudo, 1993;Minamoto et al, 1994b;Konishi et al, 1999;Rembacken et al, 2000;Kaneko et al, 2004). Therefore, inhibition of either p-MAPK or related molecule might be a new therapeutic strategy to treat these CRCs.…”
Section: Discussionmentioning
confidence: 99%
“…Most CRCs are thus believed to arise from preexisting adenomatous polyps. Most of these benign precursor lesions are of polypoid, protruding origin (Muto et al, 1975); however, many investigators have reported flat and depressed neoplasias (FDNs) as a new type of precursors of CRC and propose that these tumours develop through a de novo pathway, as they are not associated with adenoma components (Bedenne et al, 1992;Iishi et al, 1992;Kudo, 1993;Minamoto et al, 1994b;Konishi et al, 1999;Rembacken et al, 2000;Saitoh et al, 2001). Flat-depressed neoplasias are characterised by a higher potential of malignancy than protruding neoplasias (PNs) (Kudo, 1993).…”
mentioning
confidence: 99%
“…Muitos autores recomendam o uso da CE com o objetivo de aumentar a sensibilidade da colonoscopia de resolução convencional na detecção desses tipos de lesão (1,4,5,6,7,8,9,10,11,12,15) .…”
Section: Discussionunclassified
“…Com o objetivo de otimizar a detecção de lesões menores ou planas localizadas no cólon, diversos autores passaram a utilizar corantes durante a realização da colonoscopia convencional (1,4,5,6,7,8,9,10,11,12,15) . O índigo-carmim (IC) é corante habitualmente instilado sobre a mucosa colorretal, objetivando melhor visualizar lesão já detectada à colonoscopia convencional, como resultado de sua deposição sobre os orifícios que correspondem às aberturas mucosas das glândulas intestinais (Lieberkühn), levando dessa forma, a melhor definição do relevo mucoso intestinal -cromoendoscopia (CE) de contraste.…”
Section: Introductionunclassified